Pemanfaatan Media Pembelajaran Berbasis Multimedia Pada Guru Pondok Pesantren Hidayatullah Bengkulu - Yul, Fadlul Amdhi; Mesterjon; Siska , Jumiati; Selviani , Diah; Rachayu , Imma; Luthfia , Izza (Jurnal Kewirausahaan dan Bisnis, 2020)
Students are often faced with several problems in the learning process both internally and externally. One of the external problems that is often experienced by students is the problem of teachers and learning infrastructure. Problems arising from these two external problems are often interconnected. One example is when a teacher as a teacher as well as an educator is indirectly required to be able to design interesting, effective, and creative teaching materials to increase student learning interest. through cultural agents from outside the school (Budimansyah, 2010). Teachers of the Hidayatullah Islamic Boarding School, especially Middle-High School Teachers, really need training on the Utilization of Multimedia-Based Learning Media during this pandemic because all teachers are required to be more creative in creating learning processes using technology.Based on a survey of the Lecturer Team and assisted by Students in dealing with learning process problems in this 19 pandemic era, the Community Service Team carried out Community Service with the title "Utilization of Multimedia-Based Learning Media for Hidayatullah Bengkulu Islamic Boarding School Teachers".